Upaya Meningkatkan Kreatifitas Anak Usia Dini Usia 5-6 Tahun Melalui Permainan Edukatif Lego di Kober Nurul Huda Desa Sukaratu Kecamatan Banyuresmi Kabupaten Garut - Jamilah, Mimah; Munajat, Asep; Ashshidiqi , Alfian (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to explore efforts to increase the creativity of early childhood (5-6 years) through lego educational games at KOBER Nurul Huda, Sukaratu Village, Banyuresmi District, Garut Regency. The research method used is classroom action research (PTK) with a qualitative approach. The subjects of the study consisted of 15 early childhood children. Data was collected through observation, interviews, and documentation during the lego game process. Data analysis is carried out through data reduction, data display, and conclusion/verification. The results showed that lego educational games are effective in increasing early childhood creativity. Children show improvements in creative thinking skills, problem-solving skills, and collaboration skills during the lego game process. They also showed high interest and satisfaction in participating in the activity.